Kari Polanyi Levitt and Canadian Political Economy - Rioux, Michèle. author. aut Link
XVII, 70 p. 19 illus., 16 illus. in color.
Keywords: This book acts as a tribute to the legacy of the Canadian political economist Kari Polanyi Levitt, daughter of Karl Polanyi, one of the great economists of the 20th century. Polanyi Levitt’s life and work were devoted to understanding the scientific and political challenges that humanity faces and the incredible impacts of development, trade, and globalization in their diverse manifestations, including in the context of the current COVID-19 pandemic. This book reflects on Polanyi Levitt’s conviction that the solution to contemporary challenges lies not in the development of sophisticated technologies, but in questioning how we want to live with each other and working to re-embed the economy in the wider social system. Ultimately, the book contends that Polanyi Levitt’s message is simple: humanity must rethink the way we live in this world our place in the universe, and our relationship with nature. Drawing on a 10-year research project encompassing interviews and literature review, this short volume introduces and celebrates Kari Polanyi Levitt's legacy and invites political economists to engage with her work. Michèle Rioux is Full Professor at Université du Québec à Montréal and Director of The Center for Research on Integration and Globalization (CEIM), Canada. Hughes Brisson is Researcher at The Center for Research on Integration and Globalization (CEIM), Canada.